Predictors of hospital mortality among patients with COVID-19 in Tehran, Iran - Fatemeh Esfahanian; SeyedAhmad SeyedAlinaghi; Nazanin Janfaza; Marcarious M. Tantuoyir (SAGE Open Medicine, 2021)
Objective: The coronavirus disease 2019 (COVID-19) has become a global pandemic. Timely and effective predictors of survival and death rates are crucial for improving the management of COVID-19 patients. In this study, we evaluated the predictors of mortality based on the demographics, comorbidities, clinical characteristics, laboratory findings, and vital signs of 500 patients with COVID-19 admitted at Imam Khomeini Hospital Complex, the biggest hospital in Tehran, Iran. Methods: Five hundred hospitalized laboratory-confirmed COVID-19 patients were included in this study. Subsequently, electronic medical records, including patient demographics, clinical manifestation, comorbidities, and laboratory test results were collected and analyzed. They were divided into two groups: expired and discharged. Demographics, clinical, and laboratory data were compared among the two groups. The related factors with death in the patients were determined using univariate and multivariate logistic regression approaches. Results: Among the 500 hospitalized patients, most patients were male (66.4% versus 33.6%). The expired group had more patients ⩾70 years of age compared with the discharged group (32.9% versus 16.3%, respectively). Almost 66% of the expired patients were hospitalized for ⩾5 days which was higher than the discharge group (26.9%). Patients with a history of opium use in the expired group were significantly higher compared to the discharged group (14.8% versus 8.6%, p = 0.04) as well as a history of cancer (15.5% versus 4.7%, p < 0.001). Out of the 500 patients with COVID-19, four patients (2.6%) were HIV positive, all of whom expired. Dyspnea (76.4%), fever (56.6%), myalgia (59.9%), and dry cough (67%) were the most common chief complaints of hospitalized patients. Age ⩾70 years (adjusted odds ratio = 2.49; 95% confidence interval, 1.02–6.04), being female (adjusted odds ratio = 2.06; 95% confidence interval, 1.25–3.41), days of hospitalization (adjusted odds ratio = 5.73; 95% confidence interval, 3.49–9.41), and having cancer (adjusted odds ratio = 3.23; 95% confidence interval, 1.42–7.39) were identified as independent predictors of mortality among COVID-19 patients. Conclusion: Discharged and expired COVID-19 patients had distinct clinical and laboratory characteristics, which were separated by principal component analysis. The mortality risk factors for severe patients identified in this study using a multivariate logistic regression model included elderly age (⩾70 years), being female, days of hospitalization, and having cancer.